Resposta bioquímica de cultivares de soja à Meloidogyne javanica - Santos, Paulo Sergio dos (2020)
Induction of resistance has been used to control pests and plant diseases. Defense mechanisms can be activated by organic or inorganic agents, reducing the impacts caused by these organisms in crops of agricultural importance. The studies presented in this thesis aimed to elucidate the possible effects of Bacillus amiloliquefaciens and Pyraclostrobin in induction of resistance in soybean cultivars against root-knot nematode Meloidogyne javanica. In addition, we studied the time course of biochemical responses of the soybean cultivars, analyzing the initial interaction plant/nematode and using antioxidant enzymes as markers of oxidative stress. Both experiments were conducted in a greenhouse. In the first study, the effect of using B. amyloliquefaciens and Piraclostronin on induction resistance was investigated based on vegetative parameters of plant height, fresh and dry weight of the aerial part of the plants, fresh root weight, number of galls, number of nematodes per gram of root and reproduction factor. From this, it was found that both inductors provided a reduction in the number of galls, number of nematodes per gram of root and reproduction factor in the cultivars BMX-Ícone IPRO, BMX-Ativa RR, SYN-Vtop RR and NA-5909 RG. In the second study, two experiments were developed; the first with the objective of investigating, in hours, the response of the antioxidant complex of the soybean cultivar BMX-Ativa RR inoculated with three population densities of M. javanica (0; 50; 5,000 and 10,000 nematodes + eggs) submitted to five periods of exposure (1, 2, 6, 12 and 48 hours after inoculation). The second experiment consisted of four soybean cultivars (BMX-Ativa RR, NA-5909 RG, SYN-Vtop RR and BMX-Icon IPRO), four collection intervals (6, 12, 24 and 48 hours), with inoculation of 2,500 juveniles of M. javanica and without nematode inoculation. To confirm the response of the antioxidant complex resulting from the nematode / plant interaction, root staining was performed at the respective collection times to enable counting the number of juvenile nematodes penetrated. The parameters evaluated in both experiments were: the antioxidant enzymes peroxidase (POX) and ascorbate peroxity (APX), the concentrations of hydrogen peroxide (H2O2) and Malondealdehydes (MDA) and the number of juveniles of M. javanica penetrated. In experiment 1, soybean plants in the presence of M. javanica showed a significant increase in the concentration of H2O2, varying in relation to population densities and collection times and promoting the activity of the enzymes peroxidase (POX) and ascorbate peroxidase (APX). In experiment 2, the concentration of hydrogen peroxide (H2O2) varied between cultivars with and without inoculation and at different collection times. These events were evidenced by the concentration of Malondialdehydes (MDA) and the activity of antioxidant enzymes POX and APX, indicating a rapid response from the host to infection by M. javanica. Oxidative stress caused by M. javanica did not vary among soybean cultivars, regardless of their reproduction rate, however the responses of antioxidant enzymes POX and APX occurred as reproduction factor of cultivars.